Salmonella enterica Growth Conditions Influence Lettuce Leaf Internalization - Kroupitski, Yulia; Gollop, Rachel; Belausov, Eduard; Pinto, Riky; Sela (Saldinger), Shlomo (Frontiers in Microbiology, 2019)
Human pathogens on plants (HPOP) have evolved complex interactions with their plant host. Stomatal internalization is one such mode of interaction, where bacteria are attracted to stomata and penetrate into the substomatal cavity by a process mediated by chemotaxis. Internalization enables HPOP to evade the hostile environment of the leaf surface and find a protected, nutrient-rich niche within the leaf. Numerous studies have documented attachment and entry of the foodborne pathogens, Salmonella enterica and Escherichia coli into stomata. Internalization, however, varies considerably among different pathogens and in different plants, and both bacterial and plant's factors were reported to influence HPOP attachment and internalization. Here we have studied the effect of laboratory growth conditions, on the internalization of Salmonella enterica serovar Typhimurium (STm) into lettuce leaf. We have further tested the potential involvement of universal stress-proteins in leaf internalization. We found that STm grown in Luria Bertani broth devoid of NaCl (LBNS), or in diluted LB (0.5xLB) internalized lettuce leaf better (62±5% and 59±7%, respectively) compared to bacteria grown in LB (15±7%). Growth under non-aerated conditions also enhanced STm internalization compared to growth under aerated conditions. Growth temperature of 25oC and 37oC did not affect STm internalization; however, growth at 42oC, significantly augmented leaf internalization. Since, the tested growth conditions represent moderate stresses, we further investigated the involvement of five universal-stress genes in STm leaf internalization following growth in LBNS medium. Knockout mutations in ydaA, yecG, ybdQ and uspAB, but not in ynaF, significantly reduced STm internalization compared to the wild-type (wt) strain, without affecting bacterial attachment and motility. Transduction of the mutations back to the parent strain confirmed the linkage between the mutations and the internalization phenotype. These findings support a specific role of the universal-stress genes in leaf internalization. The present study highlights the complexity of bacterial internalization process and may provide partial explanation for the variable, sometimes-contrasting results reported in the literature regarding stomatal internalization by HPOP. Characterization of the regulatory networks that mediate the involvement of usp genes and the tested growth factors in STm internalization should contribute to our understanding of human pathogens-plant interactions.